3D and 4D Printing for Tissue Engineering and Regenerative Medicine - Rahman, Saeed Ur (ADVANCES IN BASIC MEDICAL SCIENCES, 2022)
Tissue engineering is an emerging field which merges different areas in order to construct biomaterials scaffolds that sustains, recover or improve the biological activities of injured or diseased tissue.1 Cell based tissue engineering techniques are currently being successfully developed to repair and restore the damaged and diseased tissue functions. The fundamental principle is the use of an appropriate cell source and a biocompatible scaffold system to construct a mimic of the targeted tissue. An additional challenge is that most organs and tissues are multiphasic in nature. Thus an ideal scaffold should be capable of supporting multi-lineage cell types.